Governança das contratações (bens e serviços): um estudo de caso na Universidade Federal do Cariri - Gonçalves, Túlio Bessa Almeida (2021)
The objective of this research was to understand how corporate governance practices are adopted in the hiring process (goods and services) at the Universidade Federal do Cariri, based on the reality perceived by managers and the evidence found. The methodology used was, therefore, a single case study, with a qualitative approach, but with quantitative aspects also analyzed. The bibliographic survey, survey through the application of a questionnaire (using the Likert scale) and documentary research were used as data collection techniques. Data treatment was carried out by content analysis, descriptive statistical analysis and document analysis, using data triangulation. The main results showed that most managers have a positive perception regarding the adoption of governance practices in UFCA hiring. However, in comparison with the evidence collected, there was a divergence of results. Of the 43 listed practices, according to the perception of managers, 29 (which represents approximately 67%) are applied, but only 18 (which represents approximately 42%) were evidenced with the documentary research. The identified strengths were mainly presented in the thematic axes of Planning, Risk Management and Contracting Work Processes. The critical points are related to Strategic Management, Integrity, Ethics, Competence Management, Contracting Policies and Guidelines. It was concluded that there is an indication that part of the managers do not have a complete knowledge of the theme of governance in public procurement and the application of its practices, as well as the possible existence of information asymmetry between those who work directly in the public procurement process and those that act indirectly or do not act. Thus, there was a need for greater investments by UFCA in the adoption of governance practices in hiring, especially with regard to the critical points presented.